Atomic‐Layered MoS2 as a Tunable Optical Platform. Issue 10 (9th August 2016) - Qin, Chengbing; Gao, Yan; Qiao, Zhixing; Xiao, Liantuan; Jia, Suotang
Abstract : Monolayer molybdenum disulfide (MoS2 ), a direct bandgap semiconductor with atomic thickness, provides significant advantages in many applications including high‐performance electronics, light emitters, and photodetectors/sensors. Controlling the electronic and optical properties of atomic‐layered MoS2 is extremely important for its practical applications. Interestingly, modulating the optical properties by physical routes, such as layer thickness, twist angle, tensile strain, temperature, gas physisorption and electrical doping, is more attractive, as these methods can control optical properties in real‐time, reversible, and in situ. The physical routes would be beneficial for understanding the fundamentals of electronic and optical properties of atomic‐layered MoS2, and also for its promising application in advanced optical materials and next‐generation electronic devices. This review highlights recent, state‐of‐the‐art research on tuning the optical properties of atomic‐layered MoS2 (including monolayer and few‐layer MoS2 ). Physical routes and proposed mechanisms of these modulations are discussed. Crystal structures and electronic band properties of atomic‐layered MoS2 are also reviewed, as they play important roles in understanding the modulation mechanisms. Finally, potential optical applications in electronic and optoelectronic devices based on tunable optical features are described, and a future prospective in this exciting field is presented. Abstract : Atomic‐layered MoS2 offers significant advantages for advanced optical materials and next‐generation electronic devices, which requires controlling its electronic and optical properties. This review highlights recent, state‐of‐the‐art research in tuning the optical properties of atomic‐layered MoS2 . Physical routes and proposed mechanisms, especially switching among quasiparticles, are discussed.